Fourier series of functions related to ordered bell polynomials - Kim, Taekyun; Kim, Dae San; Jang, Gwan-Woo; Park, Jin-Woo (Utilitas Mathematica, 2022)
In this paper, we study three types functions related to ordered Bell polynomials and derive their Fourier series expansions. In addition, we express them in term of Bernoulli functions.